Dari Yerusalem ke Ruang Siber - Debby Christ Mondolu; Obet Nego (Sekolah Tinggi Teologi SAPPI Ciranjang, 2026)
This article re-examines the theological and missiological meaning of the phrase “ends of the earth” in the Great Commission (Matthew 28:18-20; Acts 1:8) within the context of the digital age and cyberspace. Employing a qualitative-theological approach and hermeneutic-contextual analysis, it reinterprets the “ends of the earth” as an existential metaphor of global digital connectivity, where the Missio Dei continues to transcend geographical and technological boundaries. The findings reveal that cyberspace can be considered a new “mission field,” demanding strategic engagement rooted in incarnational theology, digital communication, and ethical mission practice. The study proposes cyber-missiology as a conceptual framework integrating presence, witness, and community within the digital ecosystem. It concludes that the Great Commission remains relevant and universal amidst the transformation of global communication. Thus, cyberspace is not merely a medium but a new horizon of God’s mission extending to every digital “end of the earth.”